Social neuroscience of psychiatric disorders - Manes, Facundo; Mendez, Mario F. (Social neuroscience, 2013)
This book is about the role of the social brain in neuropsychiatry. The need to belong to social groups and interact with others has driven much of the evolution of the human brain. The relatively young field of social neuroscience has made impressive strides towards clarifying the neural correlates of the social brain, but, until recently, has not focused on mental and neurological disorders. This unique and ground-breaking volume is a major step forward in deciphering the impact of the social brain on neuropsychiatric disorders. Investigators evaluate neuropsychiatric disorders in the context of recent advances in social neuroscience to reveal the impact of social brain mechanisms on neuropsychiatric disorders and allow readers to glimpse the exciting potential advances in this field in the years to come.